Lower Eocene on Majevica north of Tuzla (NE Bosnia) - Pavlovec, Rajko; Pavšič, Jernej; Vrabac, Sejfudin (Geologija, 2005)
In Lower Eocene marlstones on Mt. Majevica in northeastern Bosnia species Nummulites atacicus and N. robustus were determined, the latter first found on the Balkan Peninsula. In the beds occur next to Paleogene many redeposited Cretaceous nannoplankton species, an indication of the exposure of Cretaceous beds in Lower Eocene in the investigated area.